2002
DOI: 10.1308/135576102322527766
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a Dental Career among Successful Applicants for Dentistry Compared with those of Fifth-Year Dental Students

Abstract: Applicants appeared to have a more 'idealistic' view of dentistry than the senior students, however similarities between the responses of students and applicants are encouraging for the future of the profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 7 publications
3
33
2
Order By: Relevance
“…Comparison of medical and dental students across six dimensions of interest (status and security, nature of the occupation, career opportunities, patient care/working with people, use of personal skills and interest in science) by Crossley and Mubarik, [40] suggested that dental students were significantly more likely to be motivated by 'status and security', 'high income' and the 'nature of the occupation', when compared with their medical counterparts; whereas medical students were significantly more likely to be motivated by 'altruism' than dental students. However, the lack of altruism identified in their sample of students is not supported by other studies, [10,41,48,49] and researchers in the field. [50] None of the above studies has examined motivation in relation to all three demographic variables of sex, ethnicity and admission type, which given the changing nature of the profession is an important area for research.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Comparison of medical and dental students across six dimensions of interest (status and security, nature of the occupation, career opportunities, patient care/working with people, use of personal skills and interest in science) by Crossley and Mubarik, [40] suggested that dental students were significantly more likely to be motivated by 'status and security', 'high income' and the 'nature of the occupation', when compared with their medical counterparts; whereas medical students were significantly more likely to be motivated by 'altruism' than dental students. However, the lack of altruism identified in their sample of students is not supported by other studies, [10,41,48,49] and researchers in the field. [50] None of the above studies has examined motivation in relation to all three demographic variables of sex, ethnicity and admission type, which given the changing nature of the profession is an important area for research.…”
Section: Introductionmentioning
confidence: 60%
“…Research into the motivation and professional expectations of the emerging workforce is therefore vital to provide evidence to inform professional leadership and policy decisions. Within dentistry, such research is recognised to be especially important given the length and cost of training; [10] however, research in this field is limited and may not take account of the contemporary student intake. [11]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, the majority of students were heading to the dental profession with an idealistic vision; while with change in societies, the young generation's attitude in choosing a career has changed due to the long period of education and high costs and because of the fact that career changing is rarely possible for dentists. For these reasons those who for whatever reason are not suitable for the profession, are not professionally and psychologically satisfied (Skelly & Fleming, 2002). According to Chambers' report,20-50 percent of dentists would not choose the dental profession in the event of further chance for choosing a job (Chambers, 2001).…”
Section: Introductionmentioning
confidence: 99%